The Impact of Digital Transformation and Income Diversification on Banking Stability in Asean-5 Emerging Countries - Oktafianti, Putri Adellia; Danarsari, Dwi Nastiti (Dinasti Publisher, 2025)
This research aims to analyse the impact of digital transformation and income diversification on banking stability in the ASEAN-5 emerging countries for the period 2014-2023. In recent years, banks are dealing with digital transformation to enhance operational efficiency and offer more innovative financial services, while diversifying revenue through non-interest income sources to reduce their reliance on interest income, which is vulnerable to fluctuations in interest rates. The research employed a purposive sampling method for a sample of 80 institutions in the ASEAN-5 emerging countries (Indonesia, Malaysia, Philippines, Thailand, and Vietnam) that fulfilled certain criteria. The estimation method employed is panel data regression utilizing the Dynamic System Generalized Method of Moments (GMM) —which allows researchers to address endogeneity issues in the relationships between variables— to examine the constructed model. The research results indicate that digital transformation has a negative impact on bank stability and takes time to show its positive impact. This result shows that the adoption of technology requires a significant investment at the beginning of implementation, but over time it will enhance bank's financial stability. Second, low-income diversification tends to decrease bank stability due to reliance on a single source of income, and when banks reach a certain level of income diversification, their stability will increase due to risk spreading. Finally, the moderating effect of income diversification on the relationship between digital transformation and bank stability, indicates that stability significantly increases when banks reach certain levels of income diversification and digital adoption.